Energeticky úsporná budova rodinného domu v Třebíči - Kousalíková, Jana (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Předmětem bakalářské práce je návrh energeticky pasivního rodinného domu v Třebíči. Součástí projektu je projektová dokumentace pro stavební povolení, prováděcí projekt vzduchotechniky a koncepční studie některých TZB systémů. Pozemek se nachází v téměř rovinném terénu na jižní straně města Třebíč. Vstup na pozemek je ze severní strany a vstup do objektu ze západní strany. Navržený rodinný dům má dvě nadzemní podlaží a plochou střechu s povlakovou hydroizolací. Konstrukční systém je zděný z vápenopískových tvárnic, příčky jsou z pórobetonových tvárnic. Stropní konstrukci tvoří prefabrikované stropní panely SPIROLL. Objekt je založen na železobetonových základových pasech. Větrání objektu je navrženo jako nucené se zpětným získáváním tepla a dohřevem/dochlazováním přiváděného vzduchu. Součástí bakalářské práce je návrh zdroje tepla, bilance pitné a srážkové vody, PENB a hodnocení z hlediska stavební fyziky (tepelná technika, akustika a osvětlení).

The aim of the bachelor’s project is to design a detached passive house. The project is focused the structural and architectural design, the design some of building services, building physics and fire safety of building. The plot is situated in the south of Třebíč and terrain is almost flat. The entrance to the plot is in the north and the entrance to the house is in the west. The house has two floors and flat roof, the carport has flat green roof. On the first floor there is a wind lobby, cloakroom and utility room, hallway, guest room, bathroom and big open space which includes kitchen and living room. On the second floor there are three habitable rooms: bedroom, two children’s rooms, bathroom, toilet and two dressing rooms. The structural system consists of masonry walls. External walls are form sand-lime blocks with ETICS, load-bearing walls are from sand-lime blocks and partitions are from aerated concrete blocks. The floor slabs are from prestressed hollow core slabs and the building is based on strip foundations and permanent formwork blocks. The building services which are designed in this project are heating, mechanical ventilation, electricity service cable and stormwater management. In the house there is a mechanical ventilation unit with heat recovery. Heating is provided by air source heat pump and the stormwater is stored in the accumulation tank. Stormwater will be used to watering the garden and the excess of stormwater will be infiltration into the soil. Part of the electricity is provided by photovoltaic panels on the flat roof. The part of project is certificate of energy performance of building, rating of construction for heat conduction, acoustics, daylighting and their assessment with legislation.
Energy-saving building of a family house in Třebíč
Keywords: pasivní dům; plochá střecha; vápenopískové tvárnice; pórobetonové tvárnice; ETICS; PENB; stavební fyzika; tepelné čerpadlo; nucené větrání s rekuperací; passive house; flat roof; sand-lime blocks; aerated concrete blocks; ETICS; energy performance certificate; building physics; heat pump; mechanical ventilation with heat recovery